Analyzing the impacts of International Capital Inflows and Fiscal–Monetary Policies on Climate Change in the Asia-Pacific Region - Muhammad AZAM KHAN (Communications of International Proceedings, 2025)
Changes in weather patterns and extreme weather events pose a significant threat to economic growth and development. This study is an attempt to analyze the influences of foreign capital inflows, fiscal and monetary policy, energy use, and national income on climate change, measured by air temperature, in the ten countries from the Asia-Pacific region. Using panel data from 1990–2023, the most appropriate empirical methodologies, namely panel Autoregressive Distributed Lag (ARDL), dynamic ordinary least squares (D-OLS) and completely modified ordinary least squares (FM-OLS), and the panel Granger causality test, based on the nature of the data, are employed for empirical analysis. Empirical outcomes reveal that foreign capital inflows in the form of FDI have a climate mitigation impact, while foreign aid has a climate aggravating impact. Similarly, monetary policy through money supply has a climate mitigation impact, while fiscal policy through government spending has a climate aggravation impact. Both energy usage and national income have aggravating impacts on climate change in the region. These findings suggest that effective measures need to be taken by each national government to ensure climate change mitigation, which will ultimately impact the process of sustainable economic development. JEL Classification: F3; O23; N1
Keywords: International capital inflows; Fiscal- Monetary Policy; Asia-Pacific region